Tecnologia e educação no Ensino Médio: um estudo da implantação doPrograma Nacional de Tecnologia Educacional (PROINFO) - Mauricio Antonio Vieira (2017)
The goal of this research was to investigate the impact of the Programa Nacional de Tecnologia Educacional (ProInfo) in the High School network in the state of Minas Gerais, by verifying the pedagogical use of digital technologies in practical learning techniques, in a state school in Belo Horizonte. It meant, also, to understand, through this study, to understand data related to the Program implementation in Minas Gerais, as well as understand the use of digital technology and its influence in learning, by verifying procedures and methodology used by teachers in the HighSchool State School studied in this research, which is located in Belo Horizonte, taking as subjects, teachers and learners. The theoretical basis for this study comes from the studies of Castells (2007), Zuin (2010), Lévy (2010), Bauman (2011), Mill e Jorge (2013), Arroyo (2014), Dayrell (2014), Paula e Nunes (2014), Tavares e Gomes (2014), Moran (2014), among others. We do hope this study will contribute tounderstand the impact of ProInfo in Minas Gerais, making it possible to verify the pedagogical use of digital technologies and its implications in the learning-teaching process. Results point the TDIC - digital information and communication Technologies -, according to teachers and educators in Escola Estadual Professor Affonso Neves, has benefited from the teaching-learning process, as well as fromdigital inclusion. Nevertheless, this study suggests the need for investing in the continual training of teachers as related to the use of TDIC (DICT) in teaching practice.